2014
DOI: 10.3389/fncel.2014.00238
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor agonists modulate neuropathic pain: a link to chemokines?

Abstract: Chronic pain presents a widespread and intractable medical problem. While numerous pharmaceuticals are used to treat chronic pain, drugs that are safe for extended use and highly effective at treating the most severe pain do not yet exist. Chronic pain resulting from nervous system injury (neuropathic pain) is common in conditions ranging from multiple sclerosis to HIV-1 infection to type II diabetes. Inflammation caused by neuropathy is believed to contribute to the generation and maintenance of neuropathic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 171 publications
(274 reference statements)
0
38
0
Order By: Relevance
“…CCL-3/MIP-1α is a pro-inflammatory chemokine that participates in acute and chronic inflammatory responses by recruiting T-cells, monocytes, dendritic, and NK cells, playing an important role in the pathogenesis of many inflammatory conditions 22 . CCL-3/MIP-1α also acts as a mediator of chronic pain 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CCL-3/MIP-1α is a pro-inflammatory chemokine that participates in acute and chronic inflammatory responses by recruiting T-cells, monocytes, dendritic, and NK cells, playing an important role in the pathogenesis of many inflammatory conditions 22 . CCL-3/MIP-1α also acts as a mediator of chronic pain 23 .…”
Section: Discussionmentioning
confidence: 99%
“…This molecule is also involved in sensory regulation and neuropathic pain 23 . CCL5/RANTES has been previously shown to be higher during migraine attacks 25 , but in the present study this molecule was higher in migraine regardless of presence of pain.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, PPARγ agonists have been involved in the regulation of this adipose-specific plasma protein that possesses antiatherogenic properties [38]. Performing further analysis including other inflammatory mediators such as chemokines in the brain of SNT and ART models would be necessary to address this point [39].…”
Section: Discussionmentioning
confidence: 99%
“…Both in vitro and in vivo studies have demonstrated that neuronal PPARγ prevents COX-2 increase, which in turn may reduce prostaglandin synthesis [40]. Hence, the reduction of PPARγ in pain models might contribute towards the loss of control of COX-2 upregulation, ultimately causing pain.…”
Section: Discussionmentioning
confidence: 99%
“…Another group of endogenous ligands consists of lipid metabolites from saturated or unsaturated fatty acids. Examples of synthetic ligands that bind to PPARα are the fibrate class of hypolipidemic drugs (gemfibrozil, bezafibrate, and fenofibrate), 4-chloro-6-(2,3-xylidino)-2-pyrimidinylthioacetic acid (WY14643), some phthalate monoesters (monoethylhexyl phthalate), and herbicides (lactofen) [16,17].…”
Section: Pparα Structure and Activationmentioning
confidence: 99%